Icons - Stohl, Margaret (New York: Little, Brown and Company, 2013)
After an alien force known as the Icon colonizes Earth, decimating humanity, four surviving teenagers must piece together the mysteries of their pasts--in order to save the future.
Keywords: Science fiction; Survival -- Fiction; Insurgency -- Fiction; Extraterrestrial beings -- Fiction